Physiological exophoria did not increase the incidence of myopia in rural school children in Taiwan. Issue 25 (24th June 2022) - Hsu, Jui-Hung; Lai, Li-Ju; Tung, Tao-Hsin; Hsu, Wei-Hsiu
Abstract : Abstract: This study evaluated the incidence rate and risk factors for developing myopia in elementary school students in Chiayi, Taiwan. This prospective cohort study comprised 1816 students without myopia (grades 1 to 5 in Chiayi County). The students underwent a noncycloplegic ocular alignment examinations using an autorefractometer and completed a questionnaires at baseline and at a 1-year follow-up. A univariate logistic regression was used to assess the effects of the categorical variables on new cases of myopia. A multinomial logistic regression was then conducted. A chi-squared test was used to compare new cases of myopia in terms of ocular alignment. A Cox hazard ratio model was then used to validate factors associated with changes in ocular alignment. A P value of <.05 was considered significant. In 370 participants with new cases of myopia out of 1816 participants, a spherical error of −1.51 ± 0.6 diopters was noted at follow-up. The baseline ocular alignment was not a significant risk factor for developing myopia (exophoria vs orthophoria: OR 1.26, 95% CI 0.97–1.62; other vs. orthophoria: OR 1.15, 95% CI 0.73–1.82). However, new cases of myopia (HR 1.36, 95% CI 1.14–1.61), and baseline ocular alignment (exophoria vs orthophoria: HR 3.76, 95% CI 3.20–4.42; other vs orthophoria: HR 3.02, 95% CI 2.05–4.45) were associated with exophoria at follow-up. This study provided epidemiological data on the incidence of myopia in elementary school students in Chiayi, Taiwan. It also demonstrated that physiological exophoria does not predispose patients to developing myopia.